Visitor Perceptions of the Existence of the Tebet Eco Park City Park - Suesilowati, Suesilowati; Bachtiar, Heikal; Noegraha, Rosandi Ardhi (International Journal on Advanced Science, Education, and Religion, 2025)
Jakarta is experiencing rapid growth, leading to a reduction in green open spaces (RTH). As one of the efforts to address this issue, Tebet Eco Park (TEP) has been revitalized into an urban park that serves both ecological and social functions for the community. This study aims to analyze visitors' perceptions of TEP by examining structural and personal aspects. This research employs a mixed-methods approach, integrating both qualitative and quantitative methods. Data collection was conducted through observation, interviews with park management, and distribution of questionnaires to 60 respondents. Data analysis was performed using descriptive statistics to determine visitor perceptions based on the established aspects. The results indicate that visitors' perceptions of the structural aspect obtained an average score of 2.82, while the personal aspect received an average score of 3.13. Both aspects fall into the "agree" category, demonstrating that visitors generally have a positive perception of the park. However, there is still room for improvement in the structural aspect, particularly in the dimensions of environment, social norms, and culture. Factors such as cleanliness, public facilities, and vendor and parking management are key concerns affecting visitor satisfaction. Based on these findings, it is expected that park management will implement further improvements and developments to enhance service quality and visitor comfort at Tebet Eco Park.